Calidad de leche acopiada de pequeñas ganaderías de Cotopaxi, Ecuador - Guevara-Freire, Deysi (2019)
The compositional, physicochemical and hygienic quality of the raw milk collected in two dairy plants in Cotopaxi, Ecuador was analyzed and compared with the Ecuadorian regulations. Ten suppliers were selected per company for a total of 210 samples per dairy plant in 21 consecutive days. The compositional quality (fat) was measured with the INEN 0012 standard, for the physicochemical quality the analysis methods of the standards INEN 0009, INEN 0011, INEN 0013, CONVENIN 1315-79 were used. For hygienic quality was used the AOAC 990.12 standard and to determine antibiotic residues the AuroFlow BTS Combo Strip Test kit was used. The variables of acidity, fat, relative density, color, odor, aspect, pH and antibiotic residues showed compliance with the Ecuadorian regulations and did not show significant differences between the dairy plants. Conversely, the fat and pH content were different between the dairy plants (p<0.05). The hygienic quality of the milk reported a high count of mesophilic aerobic microorganisms (7.58E + 07 CFU/ml and 8.02E + 07 CFU/ml) without differences between dairy plants. In conclusion, most of the parameters of physicochemical and compositional quality of milk from smallholder producers are adjusted to national regulations, except for temperature and microbiological quality, results attributed to the inadequate milking and milk storage procedures.